Rapid, in situ plasma functionalization of carbon nanotubes for improved CNT/epoxy composites. Issue 110 (15th November 2016) - Malik, Rachit; McConnell, Colin; Alvarez, Noe T.; Haase, Mark; Gbordzoe, Seyram; Shanov, Vesselin
Abstract : In situ plasma functionalization during manufacturing of CNT/polymer composites. Abstract : Improved CNT/epoxy composites composed of dry-drawn, aligned and functionalized CNTs were fabricated. Dry-drawn multi-walled carbon nanotube (MWNTs) were functionalized by atmospheric pressure He/O2 based plasma during the manufacturing of the CNT sheets and epoxy resin dissolved in solvent was sprayed during the manufacturing. The extent of CNT functionalization was controlled by adjusting the plasma power and flow rate of oxygen. Functionalized CNTs were characterized by Raman, X-ray Photoelectron Spectroscopy (XPS) and contact angle testing. The % wt CNT content in the composites was controlled by adjusting the concentration of epoxy in the solution used for spraying. CNTs functionalized by 100 W plasma and 63% wt CNT content produced the best composites demonstrating 43% improvement in tensile strength and 78% improvement in modulus over composites made with pristine CNTs. High % wt CNT content in the composites allow for the creation of strong, light-weight composites demonstrating specific strength as high as 918 MPa g −1 cm −3, a 55% and 50% improvement over pristine CNT sheet and CNT/epoxy composite made with pristine CNTs, respectively.